11: EU consumer law and technology - Jabłonowska, Agnieszka (Edward Elgar Publishing, 2023)
The chapter maps the debates at the intersection of consumer law and technology and reflects on several themes deemed particularly important. It begins with a short introduction to consumer law, focusing on the European Union law. The impact of digital technologies on consumer markets is discussed thereafter, considering both the practices of online platforms and other socio-technical developments. In the remainder of the chapter the scholarly debates on several selected topics are reconstructed and reflected upon. Particular attention is drawn to the problem of exploitation through personalisation and to division of responsibility in multi-party settings. Key points are summarised and highlighted in the conclusions.